Reviews. Issue 1 (1st December 2014) - Cutajar, Alexander; Elliott, Victoria; Pike, Graham; Timpson, Nicholas
Case Studies on Diversity and Social Justice Education, Paul C. Gorski and Seema G. Pothini (2014) New York and London: Routledge and Frances, 160 pp., ISBN: 9780415658256, p/bkDiversity in Youth Literature: Opening Doors through Reading, Jamie Campbell Naidoo and Sarah Park Dahlen (eds) (2013) Chicago: American Library Association, 219 pp., ISBN 9780838911433, p/bk, £43.50Learner-Centred Education in International Perspective: Whose Pedagogy for Whose Development?, Michele Schweisfurth (2013) London: Routledge, 192 pp., ISBN: 9780415600729, h/bk, £85.00G is for Genes, Kathryn Asbury and Robert Plomin (2014) Wiley, 197 pp., ISBN: 9781118482810, p/bk £60.00